Resilience, solidarity, agency – grounded reflections on challenges and synergies. Issue 1 (2nd January 2017) - Kelly, Ute; Kelly, Rhys
Abstract: In this paper, we respond to academic critiques of resilience that suggest an inherent affinity with neoliberalism and/or the incompatibility of resilience and critical agency. Drawing on the reflections of people who have found 'resilience' a helpful conceptual tool that has informed their engagement with a challenging and unsettling context, we suggest that ideas of resilience, solidarity and agency intersect in complex and interesting ways. Following a brief discussion of our methodology, we begin with an overview of how respondents to an online survey and a series of related conversations conceptualise resilience. We go on to explore how these conceptualisations might relate to critical analysis of the status quo, and to engagement with solidarity and agency. We conclude that there is potential to link these concepts, and that thoughtful engagement with this potential, and with the tensions and questions it raises, might make valuable contributions to both theory and practice.